Subcutaneous vaccination of pregnant guinea pigs with Brucella melitensis Rev.1: a model for preliminary study the safety of vaccine candidates against small ruminant brucellosis - Rossetti, Carlos Alberto; Rossi, Ursula Amaranta; Delgado, Fernando Oscar; Castaño Zubieta, Mirta Raquel; Foster, Camila Nayla (Ediciones INTA, 2024)
Brucella melitensis is the etiological agent of small ruminant brucellosis and abortion is the only noticeable clinical sign in most cases. Vaccination with the attenuated Rev.1 strain is the best option to prevent this clinical manifestation and subsequently control the transmission of the disease. However, colonization of the genital tract in pregnant small ruminants is a common adverse effect observed in this and other brucellosis vaccine strains. Guinea pigs have demonstrated to be an excellent model for testing the immune-protection and efficacy of Rev.1 vaccine, but studies addressing the effects of this vaccine on pregnancy have not been fully explored. The goal of this study was to characterize the effects of subcutaneous inoculation of the B. melitensis Rev.1 on pregnant guinea pigs to evaluate the possibility of establishing a suitable laboratory animal model to test and compare the safety on pregnancy of novel vaccine candidates against small ruminant brucellosis. Mid-term pregnant guinea pigs were inoculated subcutaneously with three different concentrations of the Rev.1 strain and euthanized at late-term gestation (>50 days). Blood samples were taken for sero-response before the pregnant guinea pigs were euthanized, and samples for bacteriology and histopathology were collected during necropsy. The Rev.1 strain was more consistently isolated from the spleen, chorioallantoic placentas and fetal organs of animals inoculated with ≥107 CFU of Rev.1 than from those inoculated with a lower dose. Histological alterations varied from mild to moderate presence of inflammatory cells in the spleen, mammary gland and pregnant uterus. In conclusion, placental colonization and vertical transmission were observed in pregnant guinea pigs after being inoculated subcutaneously at mid gestation with Rev.1, which is similar to what was reported in pregnant small ruminants vaccinated against brucellosis. Therefore, the pregnant guinea pig would be a useful model to initially asses the safety of vaccine candidates in pregnancy and compare them with the currently available commercial vaccine for brucellosis in small ruminants.